The Ethics of Disagreement and Its Place in the Islamization of Knowledge - Engku Alwi, Engku Ahmad Zaki; Tengku Muda, Tengku Fatimah Muliana binti Tengku Muda binti (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
Disagreement about revealed knowledge were rare during the life of Prophet Muhammad since the companions could confer with him for clarifications. The articles argue that disagreement is inevitable given human diversity in language, multiplicity of hadiths, and differences of juristic traditions. The successors to the companions developed thirteen school of Islamic jurisprudence and disagreements in interpretations became more entrenched. Criteria for contemporary ethical disagreement are set out, and Islamization of knowledge proposed for unifying and strengthening the ummah.